Using a wender utah behavioral scale to assess with hindsight adults suffering from attention-hyperactivity disorder in the city of Barranquilla - Acosta López, Johan; Cervantes Henríquez, Marta L.; Jiménez Figueroa, Giomar; Núñez Barragán, Merlys; Sánchez Rojas, Manuel; Puentes Rozo, Pedro (Universidad y Salud, 2013)
Introduction: The behavioral questionnaires are effective tools to characterize the Attention Deficit Hyperactivity Disorder (ADHD) in adulthood. Objective: Determine the behavioral characteristics of adults with ADHD in retrospect by using the Wender Utah Rating Scale (WURS). Methods: The sample consisted of 102 adults from 51 nuclear families in the city of Barranquilla. The diagnosis of ADHD was conducted using a structured psychiatric interview validated in Colombia, which is also used for genetic studies of ADHD. A neurological examination and a neuropsychological evaluation were made. The cutting scores were analyzed and the effect size, sensitivity and specificity of the scale were calculated. It was found that there are clinical and statistical significant differences in WURS scores, which showed large to enormous effect sizes. Results: The scale distinguishes affected subjects from the unaffected ones, which proves the existence of ADHD symptoms in retrospect. Conclusion: It is important to highlight the WURS can be used as a tool for screening adult ADHD symptoms. However, it is necessary to complement its results with other tools for multimodal diagnostic testing.